Chief Information Officer team evolution in university hospitals: interaction of the three 'C's (CIO, CCIO, CRIO). Issue 2 (1st April 2018) - Sridharan, Shankar; Priestman, Ward; Sebire, Neil J.
Abstract : Background: The Chief Information Officer (CIO) and Chief Clinical Information Officer (CCIO) are now established senior roles in hospital practice. With increasing emphasis on optimising use of routine health data for secondary purposes and research, additional skills are required as part of the senior information officer team, particularly in academic health care institutions. Objective: To present the role of the Chief Research Information Officer (CRIO), as an emerging, and important, component of the senior information team. Method: We review recent publications describing the composition of the senior information team, including CIO and CCIO roles, and discuss the development of the CRIO as a distinct component of the team, based on the published evidence and our experience. Results: The CRIO is emerging as an additional senior role in academic healthcare institutions, whose roles include leadership of the informatics strategy and optimisation of routine data collection systems for research data use, in addition to important aspects of research data governance. Such individuals should be senior clinicians with experience in informatics, in addition to having established research expertise and knowledge of research processes, governance and academic networks. Conclusions: The CRIO is emerging as a distinct senior information leadership role in conjunction with the already established positions of CCIO and CIO, who together, can provide optimal oversight of digital activities across the organisation.